Imagining Rural Life: Schooling as a Sense of Place - Mary Bushnell (Journal of Research in Rural Education, 1999)
I present the case ofone reborn rural community populated by former urbanites. What lifestyle and values do these newcomers seek? In what ways do they locate or construct these values? In this study, a small private school provides the vehicle for adults and children to construct, communicate, and enact their idealized identities. The school provides a physical and imagined place where newcomer families negotiate their sense of rural place. The distinction between school and home values is explored asfamilies express their identities associated with public and private lives. The school also becomes the symbolic site where the former urbanites contest their sense ofrural place with their neighbors who are long-standing rural inhabitants. The predominantly upper middle class newcomers negotiate their sense ofrural place against the backdrop ofthe primarily working class old timers' concept ofrurality. Former urbanites' conception ofrural community emerges as imagined and situational.